PENGARUH SENAM KEBUGARAN TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI PUSKESMAS TAMBAH SUBUR KECAMATAN WAY BUNGUR PROVINSI LAMPUNG TAHUN 2019 - Risza Choirunissa; Suprihatin Suprihatin; Gita Usi Prastika (Jurnal Ilmu dan Budaya, 2020)
Background: Hypertension is the third leading cause of death after stroke and tubercolusis reaching 6.7%, in the elderly the most diseases are NonCommunicable Diseases, including hypertension. Fitness gymnastics at old age which is carried out routinely will increase physical activity, so that indirectly gymnastics can improve heart function and reduce blood pressure and reduce the risk of fat buildup in the walls of blood vessels so that it will maintain its elasticity. Objectives: To determine the effect of fitness exercises on blood pressure among elderly with hypertension in Tambah Subur Health Centre Way Bungur District, Lampung Province in 2019. Methodology: Using a pre-experimental approach with pretest-posttest One grup design. The sample in this study were 27 people. The sampling technique used total sampling. The research instrument consisted of observation sheets and sphygmomanometer. Data analysis using paired t-test. Results: There were significant differences before and after the intervention on the decline in systolic blood pressure in elderly hypertension with a value (p = 0,000 <0,05), and there were significant differences before and after intervention on the decline in elderly diastolic blood pressure with hypertension with a value (p = 0.008 <0.05). Conclusions and suggestions: Physical activity such as exercise can reduce blood pressure among elderly with hypertension. Therefore, health workers are expected to be able to improve health promotion about fitness exercises for the elderly to reduce the risk and complications of hypertension.